The Response From Pesantren Recognition in The Configuration of The National Education System - Bassam Abul A'la; Moh. Rifqi Rahman (AJIS: Academic Journal of Islamic Studies, 2022)
The journey of pesantren to become an educational institution recognized by, and being part of, the configuration of national education is long and winding. This study aimed to analyze the impact of pesantren recognition and response for it. The method in this study used qualitative methods with a historical approach. Data collected through document analysis and analyzed by content analysis. Regarding the research results are, first, the impact of policies that emerged from soekarno's time to Joko Widodo's time, they are; The pesantren diploma was not recognized by the Indonesian government after independence until the issuance of the pesantren law. Pesantren need to establish a new general institution in order to gain the legitimacy of the diploma. Second, Pesantren responds to national education policies in two forms. First, by establishing public institutions according to the national education framework under the Ministry of Religious Affairs or the Ministry of Education (formal). Second, incorporate the general curriculum into the pesantren curriculum periodically and evaluate the curriculum to always be in accordance with the needs and challenges of education (mu’adalah). Finally, the government's policy of issuing the pesantren law has very significant implications for financial assistance.